Characterization of NiO nanoparticles prepared using gelatin and a low-cost synthesis - Nikolić, Violeta N.; Gilić, Martina D.; Spasojević, Vojislav V. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Nanocomposite material containing NiO nanoparticles decorated on WO3 nanowires could be used for monitoring levels of H2S gas. The effectiveness of this material is mostly determined by NiO properties. The performed study presents the first stage in the preparation of modified NiO/WO3 nanocomposite material. In this article, NiO nanoparticles are prepared by a simple, low-cost method.The behavior of nano-sized NiO particles is probed by X-ray diffraction, Fourier transform Infrared Spectroscopy, Raman spectroscopy, and hysteretic measurement.
Keywords: NiO; Diffraction measurements; Spectroscopy; Nanoparticles; Materials